Cain as the Scion of Satan: The Evolution of a Gnostic Myth in the Zohar. (6th January 2016) - Yisraeli, Oded
Abstract : The relationship between kabbalistic thought and ancient gnostic ideas has been debated by numerous scholars. Early on, Gershom Scholem argued that the rise of kabbalah represents the "reappearance, in the heart of Judaism, of the gnostic tradition ." In his wake, Isaiah Tishby has posited that the concept of the sĕfirot "emerge[d] and develop[ed] from a historico-literary contact with the remnants of Gnosticism, which were preserved over a period of many generations in certain Jewish circles, until they found their way to the early Kabbalists." Joseph Dan, on the other hand, maintains that "historical connections" must not be confused with "phenomenological similarities." There is no evidence for the existence of the former, in his opinion; all that may be claimed is a typological correspondence between gnostic ideas and medieval Jewish kabbalistic mysticism. Moshe Idel likewise claims that some early Jewish motifs penetrated gnostic texts at the same time they continued to flourish within Jewish circles until they finally found form in medieval kabbalah. Yehuda Liebes has adopted a corresponding view, although he makes fruitful exegetical use of the relationship and parallels between various gnostic and Jewish sources. The issue thus remains firmly on the academic agenda.